2021
DOI: 10.3389/fpsyt.2021.723418
|View full text |Cite
|
Sign up to set email alerts
|

Parental Sensitivity and Responsiveness as Mediators Between Postpartum Mental Health and Bonding in Mothers and Fathers

Abstract: Background: There is a lack of studies that examine the complex relationship between parental mental health, parental sensitivity and responsiveness, and parent-infant bonding. This study aimed to test whether parental sensitivity and responsiveness were mediators between postpartum mental health (depression, anxiety, and stress) and parent-infant bonding in mothers and fathers.Method: Mothers (n = 427) and fathers (n = 170) of infants aged up to 1-year-old participated in an online study. The parents complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 94 publications
3
17
0
Order By: Relevance
“…These results are congruent with those of previous studies in underlining the significant role of prenatal depression in the quality of parent‐infant bonding postpartum 6,7 . Parents suffering from depression may have a compromised ability to engage in sensitive caregiving, which may in turn influence their bonding with the infant 28 . The mothers in this study reported higher levels of depressive symptoms than their partners during pregnancy and the postpartum period, which is in line with previous findings 29,30 .…”
Section: Discussionsupporting
confidence: 92%
“…These results are congruent with those of previous studies in underlining the significant role of prenatal depression in the quality of parent‐infant bonding postpartum 6,7 . Parents suffering from depression may have a compromised ability to engage in sensitive caregiving, which may in turn influence their bonding with the infant 28 . The mothers in this study reported higher levels of depressive symptoms than their partners during pregnancy and the postpartum period, which is in line with previous findings 29,30 .…”
Section: Discussionsupporting
confidence: 92%
“…The capacity of intersubjectivity can be compromised in mothers suffering from interpersonal aggression (Dayton et al, 2016) and depressive mood disorders (Bernard et al, 2018), leaving these mothers at risk for excessive parenting stress, as parenting stress is inversely associated with parental intersubjectivity (Shai et al, 2017). Impaired parental intersubjectivity can adversely affect the bonding with the spouse as well (Nakić Radoš, 2021). Fortunately, the impairment of maternal intersubjectivity can be reversed.…”
Section: Intersubjectivity Is a Hallmark Of Quality Dyadic Interactio...mentioning
confidence: 99%
“…A recent study did not find an association between recognition accuracy on CFID and self-reported parental responsiveness. However, it established that mothers with poor recognition of infant facial expression also reported poorer mother-infant bonding regarding lack of enjoyment and affection with the infant (Nakić Radoš, 2021). Nevertheless, there is some evidence that greater maternal sensitivity for positive and negative facial expressions may be associated with more positive maternal affect and behaviour during play (Donovan et al, 2007).…”
Section: Discussionmentioning
confidence: 99%